ChemInform Abstract: The Nitrogenous Hamigerans: Unusual Amino Acid‐Derivatized Aromatic Diterpenoid Metabolites from the New Zealand Marine Sponge Hamigera tarangaensis. Issue 21 (May 2015) - Dattelbaum, Jonathan D.; Singh, A. Jonathan; Field, Jessica J.; Miller, John H.; Northcote, Peter T.
Abstract Nine new nitrogenous hamigeran diterpenoids are isolated and screened for their activity against the HL‐60 cell lines.